Kajian Perifiton di Ekosistem Lamun Pantai Puding Kabupaten Bangka Selatan - Devi Ratna Sari; Wahyu Adi; Eva Utami (Universitas Bangka Belitung, 2021)
Periphyton play an important role in water productivity providers, as they can perform photosynthesis processes that can form organic substances from inorganic subtances. Periphyton attached to seagrass leaves is a factor supporting the primary productivity of seagrass area. This research was conducted in September 2018 at Puding beach south Bangka. The data collected consisted of community structure and abundance of periphyton, seagrass density, and aquatic chemical physics factors. Based on the analysis of seagrass density correlation with periphyton abundance obtained the value of coefficient of determinance (R2)= 0.9816 and correlation coefficient (r)= 0.9907 which indicates the relationship of seagrass density and periphyton abundance is positively correlated.